From Juvenile Offender Institutions to Residential Treatment Centers: Evidence of the Shifting Paradigm to Improved Youth and Community Outcomes. Issue 2 (3rd March 2016) - Mallett, Christopher A.; Boitel, Craig
Abstract : Hundreds of thousands of youth are held every year in U.S. juvenile justice detention centers and incarceration facilities. Increasingly it is known that these facility placements are at best ineffective and at worst lead to additional youth recidivism outcomes. What is most concerning, though, is that a majority of these incarcerated youth have one or more mental health/substance abuse disorders, special education disabilities, or maltreatment victimization histories—comorbid situations that negatively impact their involvement with the juvenile courts. In this article the authors summarize the epidemiology of these youth problems within the juvenile justice system. The authors then compare the outcome evidence for the youth placed in juvenile justice facilities with those placed in residential treatment centers, finding significant advantages to addressing the problems through rehabilitative efforts. Recognizing that there are a small number of serious youthful offenders who will need placement, their analysis finds that the juvenile courts must continue (or in many instances begin) reshaping their detention and incarceration facilities reliance on punishment toward a rehabilitative residential model.